Income aspirations, migration, and investments on and off the farm: Evidence from rural Tajikistan - Bloem, Jeffrey R.; Lambrecht, Isabel B. (International Food Policy Research Institute, 2023)
In places with few casual or salaried employment opportunities, investments in farm or non-farm assets may offer the main pathway to increased incomes locally, whereas others may seek alternative investment options elsewhere—as migrants. What factors, then, explain these investment choices? One theory suggests that aspirations that are ahead, but not too far ahead, of current levels provide the best incentive for promoting investment. If this theory holds, then estimates of the relationship between the aspirations gap and investment choices should take the form of a non-monotonic inverted U-shape. We test for such a relationship between the income aspirations gap and investments in migration, farm assets, and non-farm assets using data from a household survey in rural Tajikistan. We find evidence of an inverted U-shaped relationship between the income aspirations gap and measures of migration, with the strongest relationship found with international migration. Strikingly, we do not observe any association between the income aspirations gap and measures of investment in farm or non-farm assets. Exploring heterogeneity, we find that these results can vary by household poverty status and by the respondent’s gender. Investigating a possible mechanism, we find that the relationship between the income aspirations gap and migration seems to be driven by remittances, which outweigh migration costs and increase household income.